Mechanisms for protection of agricultural water resources in Dashtestan County - Farshad Razmavar; Moslem Savari (محیط زیست و توسعه فرابخشی, 2022)
The water crisis, especially in the agricultural sector, has emerged as a major concern for policymakers in developing countries. Today, however, water scarcity is one of the main deterrents in agricultural production and plays an important role in the lack of food security. Therefore, the main purpose of this study is to identify barriers to water protection and design water protection mechanisms in the agricultural sector. Due to the application of the qualitative approach in this study, Semi-structured interview with 17 farmers in Dashtestan as one of the agricultural areas with a dry climate affected by the recent drought in southern Iran were used. To analyze the results of this study, the paradigm model of Strauss and Corbin has been used to design an appropriate mechanism to overcome this crisis. Based on the analysis of the results of factors such as cultivation of irrigated crops by farmers, increasing area under cultivation, lack of budget and sufficient funds to the agricultural sector, warm weather in recent years, reduced rainfall in recent years, recent droughts, traditional irrigation system (flooding) Lack of facilities (such as loans to change the irrigation system), digging illegal wells in the area and improper water consumption culture were the most important obstacles to water protection from the perspective of farmers. Therefore, in order to get out of this problem, the identified factors were classified and analyzed in the form of 6 mechanisms: human, mental, environmental, supportive, regulatory, legal, and economic.